Winowajczyni, niewinna, femme fatale, pocieszycielka... – Muzy w twórczości wygnańczej Owidiusza - Moskalewicz, Monika (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The main purpose of this paper is to present the variable and diverse Ovid’s attitude towards Muses in his works from exile (Tristia, Epistulae ex Ponto and Ibis). The poet seeks in these goddesses both the comfort and the cause of his exile, identifies them with his poetry frequently, as their faithful servant feels deceived but also hopes that Muses can ease the anger of Augustus. The article is an attempt to analyze this complex relationship.